Hubungan Harga Diri Dengan Kecenderungan Perilaku Bullying Pada Remaja Kelas IX Di MTS Muhammadiyah 1 Malang - Agustin, Bella Arsinia; Lilla Maria; Laksana, Kurnia (Jurnal Keperawatan Muhammadiyah, 2026)
Background: During adolescence, there are several problems that occur, one of which is bullying. There are several factors that influence bullying behavior in adolescents, one of which is self-esteem. Objective: This study aims to determine the relationship between self-esteem and the tendency of bullying behavior in ninth-grade adolescents at MTS Muhammadiyah 1 Malang. This research is a quantitative correlational study with a cross-sectional approach. The sampling technique used in this study was purposive sampling with a sample size of 56 students. Data were collected using self-esteem and bullying tendency questionnaires. Data analysis was conducted using the Spearman Rank correlation test. Results: Based on data analysis, the results showed a value of r = -0.353 and a significance level of 0.008 < 0.05, which means the hypothesis is accepted. The results indicate that there is a relationship with a weak correlation strength and a negative correlation direction between self-esteem and the tendency of bullying behavior in ninth-grade adolescents at MTS Muhammadiyah 1 Malang. Conclusion: The lower the self-esteem, the higher the tendency to engage in bullying behavior. Conversely, the higher the self-esteem, the lower the tendency to engage in bullying behavior. Adolescents with low self-esteem tend to exhibit behaviors such as feeling incapable of building good relationships with others and being easily offended. As a result, these adolescents may engage in actions such as hurting, mocking, kicking, or fighting with others, which can be considered bullying behavior.